2020
DOI: 10.21203/rs.3.rs-35729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NFATc2-dependent epigenetic upregulation of CXCL14 is involved in the development of neuropathic pain induced by paclitaxel

Abstract: Background: The major dose-limiting toxicity of paclitaxel, one of the most commonly used drugs to treat solid tumor, is painful neuropathy. However, the molecular mechanisms underlying paclitaxel-induced painful neuropathy are largely unclarified. Methods: Paw withdrawal threshold was measured in the rats following intraperitoneal injection of paclitaxel. The qPCR, western blotting, protein or chromatin immunoprecipitation, ChIP-seq identification of NFATc2 binding sites, microarray analysis were performed to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Other laboratories have also reported complementary findings on the direct central nerve system (CNS) effects of chemotherapeutic paclitaxel [ 13 , 14 ], and neuropathological changes in the spinal dorsal horn neurons have therefore gained significant interest [ 15 , 16 ]. Like the peripheral neuropathological changes that occur in dorsal root ganglion neurons and distal nerve endings, the central effects of very low concentrations of chemotherapeutics are associated with the development of overt CIPN [ 8 , 17 ]. Also, like the well-documented peripheral effects, no clear preventative treatment exists, and the underlying mechanisms need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Other laboratories have also reported complementary findings on the direct central nerve system (CNS) effects of chemotherapeutic paclitaxel [ 13 , 14 ], and neuropathological changes in the spinal dorsal horn neurons have therefore gained significant interest [ 15 , 16 ]. Like the peripheral neuropathological changes that occur in dorsal root ganglion neurons and distal nerve endings, the central effects of very low concentrations of chemotherapeutics are associated with the development of overt CIPN [ 8 , 17 ]. Also, like the well-documented peripheral effects, no clear preventative treatment exists, and the underlying mechanisms need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…44 It is well-known that upregulation of CXCL14 and activation of ERK1/2 or AKt can promote neuronal excitability through the initiation of an inflammatory response. 13,25 However, there is a need for further studies on whether or not expression of GPR85 of the spinal cord is regulated by these CXCL14 and signaling pathways in BCP.…”
Section: Discussionmentioning
confidence: 99%
“…PTX induced mitochondria damage and reactive oxygen species production may result in activation of NLRP3 in ammasome in peripheral nerve, which in turn contributed to the development of neuropathic pain [9]. It is reported that the epigenetic upregulation of CXCL14 in the spinal dorsal horn contributed to the PTXinduced neuropathic pain [11]. Additionally, it has been also reported that multiple ion channels in DRG neurons are involved [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying PTX-induced neuropathic pain is complicated andrecent ndings suggested thatPTX-induced peripheral neuropathy is often associated with neuroin ammation in the peripheral nervous system [9][10][11]. For example, compared with control rats, it is found that plasma levels of IL-1α, IL-1β, IL-6, TNF-α, INF-γ and MCP-1 were signi cantly upregulated in PTX-treated rats [12].…”
Section: Introductionmentioning
confidence: 99%